Comparative Analysis of Theory of Mind Tests in First Episode Psychosis Patients - Morozova, Alexandra; Garakh, Zhanna; Bendova, Marie; Zaytseva, Yuliya (Psychiatria Danubina, 2017)
The research is based on comparative analysis of 'Hinting Task', 'Faux Pas', and 'Reading the Mind in the Eyes' tests sensitivity in detection of Theory of Mind deficits. The study included 20 subjects with schizophrenia and schizophrenia spectrum disorders with the first episode of psychosis. Every subject performed the three proposed tests. It was shown that success rate of the three tests differed significantly. The non-verbal test 'Reading the Mind in the Eyes' caused the most difficulties. The success rate percentage of this test performance correlated negatively with the severity of psychopathological symptoms evaluated according to the PANSS scale. Thus, 'Reading the Mind in the Eyes' test is the most sensitive out of the three to Theory of Mind deficits detection, which may be used for diagnostic purposes.
Keywords: schizofrenie; teorie mysli; kognitivní poruchy; Cognition Disorders; Humans; neuropsychologické testy; Neuropsychological Tests; Psychotic Disorders; Theory of Mind; lidé; Schizophrenia; psychotické poruchy